2016
DOI: 10.1080/10942912.2015.1085395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Acid- and Alkali-Aided Processes on Bighead Carp (Aristichthys nobilis) Muscle Proteins

Abstract: The objective of this study was to investigate the effects of the acid-and alkali-aided processes on bighead carp (Aristichthys nobilis) muscle protein as compared with the conventional washing method. Acid-and alkali-aided processes resulted in higher protein recoveries than conventional Downloaded by [University of Nebraska, Lincoln] at 10:00 06 October 2015A c c e p t e d M a n u s c r i p t 2 washing method. In textural profile analyses (TPA), the highest hardness and cohesiveness were observed in the gels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…α‐helices were also found to be significantly decreased in pork myofibrillar proteins subjected to multiple freeze–thaw cycles (Zhang et al., 2017). The stability of the α‐helix structure is related to hydrogen bonds between carbonyl oxygen (−CO) and amino hydrogen (NH−) in the polypeptide chain (Chang et al., 2016). Oxidation cleaves the hydrogen bond between the C = O and NH‐ groups, resulting in a decrease in the α‐helix content (Zhang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…α‐helices were also found to be significantly decreased in pork myofibrillar proteins subjected to multiple freeze–thaw cycles (Zhang et al., 2017). The stability of the α‐helix structure is related to hydrogen bonds between carbonyl oxygen (−CO) and amino hydrogen (NH−) in the polypeptide chain (Chang et al., 2016). Oxidation cleaves the hydrogen bond between the C = O and NH‐ groups, resulting in a decrease in the α‐helix content (Zhang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A sharp decrease of the total SH content in the gel samples usually indicates the formation of S-S bond. [41] Therefore, the results demonstrated that the S-S bond plays a vital role in the oxidation of protein. Protein oxidation leads to exposure of some of the hydrophobic groups which enhanced protein surface hydrophobicity.…”
Section: Studymentioning
confidence: 92%
“…The integrity of MPs is a key factor affecting gel properties. [41] The decrease in gel strength can be attributed to deterioration of the protein structure in MP gel. Similar findings were reported by Wang et al, [42] who found heat exposure decreased the gel strength of MP gels.…”
Section: Effects Of Oxidation On Textural Properties and Water Holdinmentioning
confidence: 99%
“…The common production methods for surimi are water washing and the acid‐base method (Chang et al., 2016, 2017). The water washing method is often used to produce fish surimi.…”
Section: A Feast On Chinese Tablesmentioning
confidence: 99%